2017
DOI: 10.1007/s00338-017-1586-5
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of corals on temperate reefs: direct and indirect effects of marine heatwaves

Abstract: Globally, many temperate marine communities have experienced significant temperature increases over recent decades in the form of gradual warming and heatwaves. As a result, these communities are shifting towards increasingly subtropical and tropical species compositions. Expanding coral populations have been reported from several temperate reef ecosystems along warming coastlines; these changes have been attributed to direct effects of gradual warming over decades. In contrast, increases in coral populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 60 publications
7
59
1
Order By: Relevance
“…Globally, tropicalised shallow reefs share two key phenomena: a loss of temperate seaweed forests as the dominant habitat formers and increases in tropical/subtropical species. Different regions, however, differ in which taxa end up dominating the seafloor, with three potential trajectories identified for warming temperate reefs globally (Figure ): Seaweed‐dominated reefs (e.g., Japan)—these systems may emerge if tropical seaweed species (Figure b) replace temperate canopy‐formers, as in some southern Japan reefs (Tanaka, Taino, Haraguchi, Prendergast, & Hiraoka, ; Terazono et al, ) or, hypothetically, such a system may develop if some temperate seaweeds adapt to their new environment and persist into the future. Turf‐dominated reefs (e.g., eastern Mediterranean)—these systems are characterised by low structural complexity and simplified food webs, as canopy seaweeds become replaced by low‐biomass turfing algae (Figure c; Vergés, Tomas, et al, ; Filbee‐Dexter & Wernberg, ) Turf‐ and coral‐dominated reefs (e.g., Japan, Australia, Korea)—in these systems warm‐temperate corals and/or range‐expanding tropical corals coexist with turf algae (Figure d), which have replaced seaweeds as the dominant primary producers (Tuckett et al, ; Vergés et al, ; Wernberg et al, ; Yamano, Sugihara, & Nomura, ). …”
Section: Trajectories For Warming Tropicalised Reefsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, tropicalised shallow reefs share two key phenomena: a loss of temperate seaweed forests as the dominant habitat formers and increases in tropical/subtropical species. Different regions, however, differ in which taxa end up dominating the seafloor, with three potential trajectories identified for warming temperate reefs globally (Figure ): Seaweed‐dominated reefs (e.g., Japan)—these systems may emerge if tropical seaweed species (Figure b) replace temperate canopy‐formers, as in some southern Japan reefs (Tanaka, Taino, Haraguchi, Prendergast, & Hiraoka, ; Terazono et al, ) or, hypothetically, such a system may develop if some temperate seaweeds adapt to their new environment and persist into the future. Turf‐dominated reefs (e.g., eastern Mediterranean)—these systems are characterised by low structural complexity and simplified food webs, as canopy seaweeds become replaced by low‐biomass turfing algae (Figure c; Vergés, Tomas, et al, ; Filbee‐Dexter & Wernberg, ) Turf‐ and coral‐dominated reefs (e.g., Japan, Australia, Korea)—in these systems warm‐temperate corals and/or range‐expanding tropical corals coexist with turf algae (Figure d), which have replaced seaweeds as the dominant primary producers (Tuckett et al, ; Vergés et al, ; Wernberg et al, ; Yamano, Sugihara, & Nomura, ). …”
Section: Trajectories For Warming Tropicalised Reefsmentioning
confidence: 99%
“…Although tropicalisation is a global and increasingly visible phenomenon (Vergés, Steinberg, et al, 2014), the overall consequences of these changes for ecosystem functions or services like primary production, nutrient cycling or fisheries production are poorly understood. As well as the loss of temperate species, tropicalisation also entails the range expansion of tropical habitat-forming species like corals (Tuckett, Bettignies, Fromont, & Wernberg, 2017) and the development of novel coral reef ecosystems (Graham, Cinner, Norström, & Nyström, 2014). Thus, a key question for understanding and managing these systems is: Will the functioning of novel tropicalised systems in time become similar to tropical habitats, such as coral reefs, or should entirely new ecosystem functions be expected?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore under a warmer future, temperature increase alone, may not make high latitudes any more suitable for coral performance than current conditions. However temperature increases have already indirectly alleviated competition with seaweeds at high latitude (Vergés et al, 2014;Tuckett et al, 2017), and its role in mitigating other limiting factors (e.g., light) has been proposed (Sommer et al, 2017). It has not been established if other environmental conditions are limiting these species, and if so, what the implications are for coral performance on these reefs in a warmer future.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rates of ocean warming since the mid-1990s have remained constant at 1.5°C per 100 yr (Hobday & Pecl 2014) and there is evidence of an associated poleward shift in some tropical and subtropical coral reef species (Verges et al 2014, Wernberg et al 2016, including scleractinian corals (Thomson 2010, Yamano et al 2011, Baird et al 2012. However, there is also evidence that coral assemblages on high latitude reefs do not conform to the same rules of assembly as corals on low latitude coral reefs (Bellwood & Hughes 2001, Sommer et al 2014, and recent research has demonstrated not just a poleward shift in the distribution of tropical coral species, but an increasing abundance of resident coral species on some high latitude reefs (Tuckett et al 2017). Therefore, a better understanding of the biology of species on high latitude reefs is required to assess their potential as sites of refuge from ocean warming.…”
Section: Introductionmentioning
confidence: 99%